Effect of Knowledge, Peer Group, Family, Cigarette Price, Stipend, Access to Cigarette, and Attitude, on Smoking Behavior - R. Asto Soesyasmoro; Argyo Demartoto; Rita Benya Adriani (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Passive smokers inhale 75% of ambient smoke and 50% of exhaled smoke. A cigarette contains 4.000 poisonous chemical agents, at least 69 of which are carcinogenic. Therefore ambient tobacco smoke is detrimental to health. The purpose of this study was to analyze the effect of knowledge, peer group, family, cigarette price, stipend, access to cigarette, and attitude, on smoking behavior.Subjects and Method: This was an analytic and observational study with cross sectional design. This study was conducted at School of Health Polytechnics, Surakarta, Central Java. A total of 105 male students was selected for this study. The dependent variable smoking status. The independent variables knowledge, peer group, family, cigarette price, stipend, access to cigarette, and attitude. The data were collected by a set of questionnaire, and were analyze by logistic regression model. Results: High smoking peer group (OR= 3.21; 95% CI=1.18- 8.72; p= 0.022), high stipend (OR= 3.66; 95% CI= 1.28-10.49; p= 0.016), convenient access to cigarette (OR= 3.02; 95% CI= 1.04 to 8.73; p= 0.042) increased the likelihood of smoking. High knowledge about tobacco smoking (OR= 0.35; 95% CI=0.13-0.95; p = 0.039) and non-smoking family (OR= 0.16; 95% CI=0.03 to 0.70; p= 0.015) decreased the likelihood of smoking. High price of cigarette (OR= 0.86; 95% CI= 0.23 to 3.19; p= 0.819) and possitive attitude (OR= 0.88; 95% CI= 0.33 to 2.36; p= 0.795) did not show statistically significant effect on smoking.Conclusion: Smoking peer group, stipend, access to cigarette increase the probability of smoking. Knowledge about tobacco smoking and non-smoking family decrease the probability of smoking.Keywords: knowledge, peer group, family, cigarette price, stipend, access to cigarette, attitude, smoking behaviorCorrespondence: R. Asto Soesyasmoro.School of Health Polytechnics, Surakarta. Email: asto_monti@yahoo.co.id.Journal of Health Promotion and Behavior (2016), 1(3): 201-210https://doi.org/10.26911/thejhpb.2016.01.03.07